Understanding farmers' risk perception to drought vulnerability in Balochistan, Pakistan - Hashim Durrani; Ainuddin Syed; Amjad Khan; Alam Tareen; Nisar Ahmed Durrani; Bashir Ahmed Khwajakhail (AIMS Agriculture and Food, 2021)
Frequent occurrence of drought is a major challenge to the farmers in the drought prone district of Balochistan province, Pakistan. The agricultural communities are facing threat to agricultural production and livestock due to socio-economic drought in the study area. The Socio-economic drought refers to the conditions in which water supply flops sustaining water demand, resulting in adverse effects on society, economy and environment. The intensity of drought impacts is normally analyzed through meteorological, agricultural and hydrological indices. However, this paper presents a study based on interviews to analyze farmer's risk perceptions, attitude and awareness towards socio-economic drought and risks associated with it. The study relies on a survey of 265 farm households, following a structured questionnaire, focus group discussions and key informant interviews. Results of the study revealed that farmers perceived a continuous variability in climate for the last two decades and identified drought as the most prevalent disaster in the region. Economic reliance on agriculture and livestock, abolishment of surface water resources, depletion of groundwater and insufficient supply of electricity has further increased their vulnerability to drought. Reduction in agriculture and livestock production as well as loss of employment were the immediate economic impacts of the socio-economic drought in the study area. Social impacts such as migration to other places, increase in social crimes, drop out of schoolchildren and impacts on health and festivals were also reported. The environmental impacts included constant increase in temperature, decrease in rainfall intensity and non-climatic factors. Understanding of farmer's risk perception to drought vulnerability may contribute in assisting policy makers for the most appropriate intervention strategies.